The sustainable impacts of teacher action research on EFL teachers in Indonesia - Yunita Puspitasari; Utami Widiati; Saiful Marhaban; Teguh Sulistyo; Rofiqoh Rofiqoh (Universitas Syiah Kuala, 2021)
Action research has been a prominent topic in continuous professional development literature. Studies have evidenced its potentials for teachers, but not many have discussed the sustainability of the research as a means of Teacher Professional Development (TPD) as well as its sustainable impact. Underpinning the issue of sustainability, the present study aims at investigating what factors made the teachers choose to continue conducting teacher action research, and what pedagogical and professional competences perceived changed as sustainable impacts of Teacher Action Research (TAR). This qualitative study with a phenomenological undertone adapted Seidman’s framework to conduct in-depth interviews with five English as a Foreign Language (EFL) teachers. The results showed that motivation and self-efficacy belief, institutional supports, and collaboration with academics/universities were essentials for sustainable engagement with the research. Pedagogically, the teachers increased their awareness of the students’ characteristics, knowledge of effective learning, and ability to carry out reflective teaching. In terms of professional competence, they felt very confident and were able to make more publications. This study implies that TAR is a model of TPD that is able to develop EFL teachers’ professionalism where they can establish a better practice and develop themselves as professionals and individuals on daily basis, without leaving their students.